2021
DOI: 10.1186/s42774-021-00079-6
|View full text |Cite
|
Sign up to set email alerts
|

A low-boom and low-drag design method for supersonic aircraft and its applications on airfoils

Abstract: Sonic boom reduction has been an urgent need for the development of future supersonic transport, because of the heavy damage of noise pollution. This paper provides a novel concept for supersonic aircraft to reduce the sonic boom and drag coefficient, wherein a suction slot near the leading edge and an injection slot near the trailing edge on the airfoil suction surface are opened. To make sure of a zero net mass flux flow control, the mass flow sucked in near the leading edge is equal to the mass flow injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Another system for sonic boom reduction was presented in 2021 by Ye et al [224]. It consists of equipping the wing leading edge with a suction slot and the trailing edge with an injection slot as shown in Figure 38.…”
Section: Flow Suction and Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another system for sonic boom reduction was presented in 2021 by Ye et al [224]. It consists of equipping the wing leading edge with a suction slot and the trailing edge with an injection slot as shown in Figure 38.…”
Section: Flow Suction and Injectionmentioning
confidence: 99%
“…In the end, in 2021, another reduction concept was presented by Ye et al [224]. The idea consists of equipping the wing leading edge with a suction slot and the trailing edge with an injection slot.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Recently, other strategies have been patented, and their nuisance reduction potential shall be properly investigated before introducing new regulations. These novel approaches include the introduction of a nose spike [91,92], the adoption of shock wave dispersion techniques [93], the introduction of anti-boom jet streams [94], suction/injections wing slots [95], sonic boom suppression techniques using pulse energy addition [96], etc.…”
Section: Supersonic En-route Noise: the Sonic Boommentioning
confidence: 99%
“…Studies have shown that for a subsonic aircraft in cruise state, the friction drag of turbulent boundary layer accounts for 50% of the total drag, and every 1% reduction in drag can reduce fuel consumption by 0.75% [2]. Even under flight conditions dominated by shock drag in a supersonic/hypersonic flow, the turbulent friction drag still accounts for about 30% of the total drag [3,4]. Therefore, using appropriate flow control techniques to achieve the drag reduction of the turbulent boundary layer will greatly increase the range of the hypersonic flight vehicle under the same fuel consumption, which is of great significance for reducing the carbon emission content as well.…”
Section: Introductionmentioning
confidence: 99%